2021
DOI: 10.1007/s00125-021-05510-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal vitamin B12 and folate levels in early pregnancy with gestational diabetes: a prospective UK cohort study (PRiDE study)

Abstract: Aims/hypothesis The prevalence of gestational diabetes mellitus (GDM) is increasing worldwide in all ethnic groups. Low vitamin B12 and low/high folate levels may contribute to GDM risk, but there is conflicting evidence. Our aim is to assess the relationships of early pregnancy vitamin B12 and folate levels with the risk of GDM status at 26–28 weeks of gestation. Methods This was a prospective, multi-centre, multi-ethnic cohort study (n = 4746) in the UK.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 51 publications
3
70
0
Order By: Relevance
“…We found that serum folate levels are positively correlated with blood glucose levels and significantly associated with GDM risk in a dose-response manner. Our findings were consistent with recently published results [ 16 , 36 ], which indicated that higher maternal folate during pregnancy is associated with increased GDM risk.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that serum folate levels are positively correlated with blood glucose levels and significantly associated with GDM risk in a dose-response manner. Our findings were consistent with recently published results [ 16 , 36 ], which indicated that higher maternal folate during pregnancy is associated with increased GDM risk.…”
Section: Discussionsupporting
confidence: 94%
“…However, inconsistent findings were found for prepregnancy habitual intakes of folate in the Nurse’s Health Study [ 11 ]. Although folic acid intake evaluated via the questionnaire may not accurately reflect folate levels in pregnant women, serum and red blood cell folate levels have also been associated with GDM [ 10 , 16 ]. Our preliminary study indicated that higher folate levels in mid-pregnancy can slightly increase maternal GDM risk [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, research suggests that there are disease implications associated with vitamin B 12 deficiency, especially in vegetarian populations [15][16][17], in pregnancy [18,19], in the elderly [20], and in developing countries [19].…”
Section: Introductionmentioning
confidence: 99%
“…Also, vitamin D has effects on genome wide DNA methylation levels and was recently reported to influence long-chain polyunsaturated fatty acids and oxidative stress in the placenta via one-carbon metabolism (37). The relations between nutritional factors and the methylation of regulatory cytokines in placenta is likely very complicated, where not only the level of each nutritional factor itself, but also the combination of different factors may be important (38,39). Differences in vitamin levels could also be proxy measures of other complex life-style factors.…”
Section: Discussionmentioning
confidence: 99%